Peningkatan Ketrampilan Motorik Kasar Anak Melalui Metode Pembelajaran Sentra Balok di TK Al-Amin Palur - Anis Fitria (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
The purpose of this study is to improve gross motor skills in early childhood through the block center learning method. This research employs a qualitative method with a case study approach aimed at gaining an in-depth understanding of an individual, group, or institution. The data collection techniques used include observation, interviews, and documentation to obtain concrete data related to the issues in this study. The findings indicate that learning at the block center using block media to enhance the imagination of early childhood has numerous benefits. By considering children's readiness to learn, interests, and learning styles, this approach not only develops social skills, such as empathy toward others and the environment, self-confidence, and interaction with peers and teachers but also fosters good communication skills, politeness, and proper use of body functions. Gross and fine motor movements in children can develop effectively through this method.